Exact integration in the boundary element method for two-dimensional elastostatic problems - Zhang, X.; Zhang, X.
This paper derives the exact integrations for the integrals in the boundary element analysis of two-dimensional elastostatics. For facilitation, the derivation is based on the simple forms of the fundamental functions by taking constant, discontinuous linear and discontinuous quadratic elements as examples. The efficiency and accuracy of the derived exact integrations are verified against five benchmark problems; the results indicate that the derived exact integrations significantly reduces the CPU time for forming the matrices of the boundary element analysis and solving the internal displacements.
Keywords: EXACT INTEGRATIONS; DISCONTINUOUS BOUNDARY ELEMENT; FUNDAMENTAL FUNCTIONS; TWO-DIMENSIONAL ELASTOSTATICS